2004
DOI: 10.1002/chem.200305349
|View full text |Cite
|
Sign up to set email alerts
|

Magneto‐Structural Characterization of Metallocene‐Bridged Nitronyl Nitroxide Diradicals by X‐Ray, Magnetic Measurements, Solid‐state NMR Spectroscopy, and Ab Initio Calculations

Abstract: Crystallization of ferrocene and ruthenocene substituted in the 1- and 1'-positions by two nitronyl nitroxide radicals gave the new crystal phases beta-1 (besides the known phase alpha-1), alpha-2, and beta-2 whose structures were determined by X-ray analysis. In beta-1 the radical moieties adopt transoid positions, whereas two different cisoid conformations are adopted by alpha-2 and beta-2. These conformations result from inter- and intramolecular hydrogen bonds, respectively. All compounds experience antife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 66 publications
0
35
0
Order By: Relevance
“…Chemical and electrochemical oxidation of [M I (HBPz' 3 )(CO)(L)] (P z ¼ pyrazolyl) and [Rh I (HCPz' 3 )(CO)(L)] þ complexes has recently been described [L ¼ CO, PPh 3 , PCy 3 , P(NMe 2 ) 3 , P(p-tolyl) 3 , P(m-tolyl) 3 , P(OPh) 3 , AsPh 3 ], in which HBPz' 3 represents a tris-pyrazolylborate anion and HCPz' 3 represents the neutral carbon equivalent (Fig. 14) (42)(43)(44)(45)(46).…”
Section: E Pyrazolyl-type Rh(ii) and Ir(ii) Carbonyl Complexesmentioning
confidence: 99%
See 2 more Smart Citations
“…Chemical and electrochemical oxidation of [M I (HBPz' 3 )(CO)(L)] (P z ¼ pyrazolyl) and [Rh I (HCPz' 3 )(CO)(L)] þ complexes has recently been described [L ¼ CO, PPh 3 , PCy 3 , P(NMe 2 ) 3 , P(p-tolyl) 3 , P(m-tolyl) 3 , P(OPh) 3 , AsPh 3 ], in which HBPz' 3 represents a tris-pyrazolylborate anion and HCPz' 3 represents the neutral carbon equivalent (Fig. 14) (42)(43)(44)(45)(46).…”
Section: E Pyrazolyl-type Rh(ii) and Ir(ii) Carbonyl Complexesmentioning
confidence: 99%
“…These species were analyzed by EPR spectroscopy in frozen solution (Table VI). Except for the P(OPh) 3 ligand, all frozen solution spectra revealed resolved N and Rh hyperfine patterns for the g z component. This, together with the g values g x , g y > 2 and g z $ 2 (see Fig.…”
Section: E Pyrazolyl-type Rh(ii) and Ir(ii) Carbonyl Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…3.6 Å (Figure 1). The overall structure can also be viewed as alternating layers of [W 6 O 19 ] 2-anions and cationic free radicals. The organic layers are very well isolated, the shortest distance between nitroxide functionalities being greater than 8 Å.…”
Section: Resultsmentioning
confidence: 99%
“…Usually, ferromagnetic interactions have been ascribed to intermolecular contacts between atoms carrying spin densities of opposite signs (McConnell I proposal) [5]. This model is an easy-to-use tool, since spin densities can be obtained experimentally (NMR or polarized neutron diffraction methods) in the solid state [6]. However, it has been shown that McConnell I model fails to predict the magnetic behaviour of numerous crystalline assemblies of NN radicals [7].…”
Section: Introductionmentioning
confidence: 99%